The determinants mostly disclosed by companies that are members of the Carbon Disclosure Project - Faria, Juliano Almeida de (2018)
Concerns about climate change as a result of anthropic actions have led to an increase in the volume of information disclosed about it in the reports of companies that are members of the Carbon Disclosure Project (CDP). In this context, the factors most disclosed remain obscure due to both the complexity of climate change impacts and the stakeholders’ different interests.This study aims to identify which factors are most disclosed in the reports of companies that are members of CDP. For this purpose, it is necessary to investigate if the factors indicated by managers and experts are the main ones disclosed in the reports of companies that are members of CDP. For this purpose, it is necessary to investigate if the factors indicated by managers and experts are the main ones disclosed in the reports of, Brazilian companies that are members of CDP, as well as to identify which companies stand out in climate change disclosure based on these factors. To this end, 463 reports submitted by 48 companies between 2014 and 2016 were examined and 32 factors were investigated using the NVivo® software. Some companies submitted reports with unified titles, which reduced the sample. The results indicate that certain factors—prevention of pollution, prevention of loss, management of environmental assets, volume of greenhouse gas (GHG) emissions, and climate change strategy—account for 50.03% of the total volume of information disclosed about climate change. The main lesson learned from this research is that climate change mitigation strategy is strongly supported by the evidence of corporate annual reports, and it has relation with the following determinant factors: pollution prevention, loss prevention, environmental asset management, GHG emissions, and the strategy chosen by the companies to deal with climate change. Due to the low volume of research related to loss prevention and pollution prevention, we have identified that little attention has been paid to these items. Based on our results, we recommend that climate change mitigation strategies begin to consider these determinant factors in their structure because both have a strong influence in demonstrating how companies are managing these factors for stakeholders. Therefore, companies can benefit from this data to manage their resources for the maintenance of the social contract (legitimacy) through the factors most disclosed, especially companies with lower scores on the scale of ranking presented. Hence, stakeholders can have access to more information on strategies that mitigate climate change and help companies improve the disclosure of the actions that contribute to reduction of GHG emissions.